PREVALENSI ASPERGILLUS FUMIGATUS PADA PENJUAL KACANG TANAH DAN JAGUNG KOTA BENGKULU - Marlina, Leni (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
Aspergillus fumigates infection in peanut and corn sellers may arise due to the behavior of sellers of raw food materials which is not good. The behavior of how the storage and use of raw food materials and Personal Protective Equipment (PPE), is a behavior that must be considered. PPE is a self-protection tool that can be used for work in order to protect themselves and others, while the storage method is the treatment of raw food materials. The purpose of this study was to determine the Aspergillus fumigates infection associated with peanut and corn seller behavior in market town of Bengkulu.This research is an analytic survey research using cross-sectional design. In this study, the population was the whole peanut and corn seller in the market of Bengkulu were 30 people. Samples in Panorama Market were 10 sellers of peanuts and 5 corn sellers. The data was collected using primary data on the presence or absence of the fungus Aspergillus fumigates in seller’s sputum which obtained from laboratory tests. Then performed a collection of data about how to storage and use of masks by observation. Data analysis was done analytically using the chi-square test.The results showed the majority (53.3%) prevalence of the fungus Aspergillus fumigates. There was a significant correlation between the behavior of the storage of peanuts and corn and the use of masks by the behavior of sellers in the market of Bengkulu. There is no determinant highly influential on the cause of the two variables.For the merchant of peanut and corn should further enhance self-protection such as the use of appropriate PPE in order to avoid infection fungal pathogens such as Aspergillus fumigates.